Singapore’s effectiveness in promoting pro-environmental behaviour : a look at climate change education - Lim, Isabelle Szu Wen (Nanyang Technological University, 2020)
In this review, we analyse Singapore’s overall stance and strategies employed to combat the global issue of climate change. We observe that most of Singapore’s existing strategies are primarily state-driven and this alludes to the possibility that Singaporeans, on an individual level, may not be behaving pro-environmentally or have yet to form such habits. Singaporeans’ responses, gathered through surveys regarding environmental practices and pro-environmental campaigns, confirm this lack of pro-environmental behaviour (PEB). For this reason, we took a close look at the key determinants of PEB. Upon closer examination, it appears that knowledge, on top of its direct effects, can indirectly promote PEB through its influence on other psychological factors. This observation prompted us to consider the educational sphere of climate change response in Singapore and evaluate its effectiveness in imparting environmental knowledge. We contend that the implementation, content, and approach towards Climate Change Education (CCE) in Singapore can be further improved. Drawing from both environmental and educational psychology theories, we organised a set of recommendations in response to these limitations that educational institutions may refer to or employ. Future studies may choose to explore other possible means through which education can promote pro-environmental behaviour within Singapore other than the transmission of information, such as the reforming of perceived norms.